PATHOPHYSIOLOGY OF MYOCARDIAL INFARCTION - Razhabova Zebiniso Safarovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract:Myocardial infarction (MI), commonly known as a heart attack, occurs due to the sudden occlusion of a coronary artery, leading to ischemia and necrosis of the myocardial tissue. It is a major cause of morbidity and mortality worldwide. This article discusses the underlying mechanisms, including atherosclerosis, plaque rupture, thrombosis, and inflammatory responses, that contribute to MI pathophysiology.